Animals as Parables in the Qur'an in the Context of Human Behavior in the Modern Era - Hidayat, Fajar; Elhady, Aminullah; Faizin, Khoirul (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to examine animals used as parables in the Qur'an and their relevance to human behavior in the modern era. The method used is thematic interpretation by compiling verses containing animal metaphors, then analyzing their meanings and moral messages, and relating them to contemporary social phenomena. The results show that the Qur'an presents parables through various animals such as mosquitoes, dogs, livestock, flies, spiders, and donkeys. Each animal symbolizes human behavior, for example, dogs represent greedy and dissatisfied people, while spiders symbolize the fragility of relying on anything other than Allah. In the modern context, these parables can be linked to phenomena such as hedonism, moral decadence, consumerist lifestyles, the fragility of social media relationships, and the importance of productivity and discipline. Thus, this study confirms that animal parables in the Qur'an are not only relevant at the time of their revelation but also serve as a mirror for modern human behavior, as well as a reminder to make the Qur'an a guide for life that is relevant throughout the ages.